The Historical Evolution Of State Policy Supporting Women’s Entrepreneurship In Karakalpakstan - Nabira Nurullaeva (Pubmedia Social Sciences and Humanities, 2026)
The objective of this article is to analyze the formation and historical development of state policy supporting women’s entrepreneurship in Karakalpakstan and to identify its main stages and outcomes. The study applies historical research methods, including chronological, comparative, and contextual analysis, treating state policy as a dynamic historical process shaped by institutional change and evolving social needs. The findings demonstrate that state support for women’s entrepreneurship in Karakalpakstan has developed gradually. During the Soviet period, women’s economic activity was limited and largely regulated within centralized economic structures. In the post-independence period, state policy became more structured and institutionalized, introducing legal, financial, and organizational mechanisms aimed at encouraging women’s participation in entrepreneurial activity. These policies contributed to increased involvement of women in small-scale business, particularly in family-based enterprises and service-oriented sectors, and helped expand employment opportunities in the region. Despite these positive developments, women’s entrepreneurship in Karakalpakstan remains predominantly concentrated at the micro-enterprise level. This indicates the persistence of institutional, economic, and social constraints that limit business growth and diversification.The article concludes that state policy supporting women’s entrepreneurship in Karakalpakstan represents a consistent historical process oriented toward social stability and regional development. The historical perspective underscores the importance of adapting state policy instruments to specific regional conditions in order to improve their long-term effectiveness.